Harry Innes papers - Innes, Harry, 1752-1816.
Correspondence, financial, business, and legal papers, biographical and genealogical material, printed matter, and other papers of Harry Innes, his wife Ann Shields Innes, and various members of the allied Thomas Todd family. Includes material relating to Innes's commissary work in Virginia during the Revolution and his duties as a U.S. district judge in frontier Kentucky, particularly his role in cases relating to land claims and surveys. Other topics include the Burr conspiracy, Innes's interest in developing manufacturing in Kentucky, and family and business affairs.
Correspondents include John Aylett, John Brown, Wilson Miles Cary, Henry Clay, Joseph Hamilton Daveiss, William Davies, Benjamin Harrison, William Henry Harrison, Thomas Jefferson, Henry Knox, Henry Lee, James Madison, Humphrey Marshall, John May, George Nicholas, Edmund Pendleton, Elizabeth Pringle, Beverley Randolph, Benjamin Sebastian, Peyton Short, John Taylor, James Wilkinson, and Peachey Wills.
Lawyer and jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aylett, John -- Correspondence; Brown, John, -- 1757-1837 -- Correspondence; Cary, Wilson Miles, -- 1734-1817 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Daveiss, Joseph Hamilton, -- 1774-1811 -- Correspondence; Davies, William, -- active 1775-1781 -- Correspondence; Harrison, Benjamin, -- approximately 1726-1791 -- Correspondence; Harrison, William Henry, -- 1773-1841 -- Correspondence; Innes, Ann Shields; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Knox, Henry, -- 1750-1806 -- Correspondence; Lee, Henry, -- 1756-1818 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Marshall, Humphrey, -- 1760-1841 -- Correspondence; May, John, -- 1748-1812 -- Correspondence; Nicholas, George, -- 1754?-1799 -- Correspondence; Pendleton, Edmund, -- 1721-1803 -- Correspondence; Pringle, Elizabeth -- Correspondence; Randolph, Beverley, -- 1754-1797 -- Correspondence; Sebastian, Benjamin, -- 1745-1834 -- Correspondence; Short, Peyton, -- 1761-1825 -- Correspondence; Taylor, John, -- 1753-1824 -- Correspondence; Todd, Thomas, -- 1765-1826.; Wilkinson, James, -- 1757-1825 -- Correspondence; Wills, Peachey -- Correspondence; Todd family; Burr Conspiracy, 1805-1807.; Courts -- Kentucky; Land tenure -- Kentucky; Practice of law -- Kentucky; Kentucky -- History -- To 1792.; Kentucky -- History -- 1792-1865.; Kentucky -- Manufactures; Kentucky -- Surveys; Virginia -- History -- Revolution, 1775-1783.; Jurists; Lawyers